Evidências da relação entre evolução da gestão ambiental e a adoção de práticas de Green Supply Chain Management no setor eletroeletrônico brasileiro - Jabbour, Ana Beatriz Lopes de Sousa [UNESP] (Business Department, School of Economics, Business & Accounting USP, 2014)
The objective of this research is to examine if the environmental management evolution is positively related towards the adoption of green supply chain management practices (GSCM) by companies in the electronics sector in Brazil. To reach this objective, a quantitative research was conducted by survey with 100 companies in the electronics sector in Brazil. The collected data were processed using descriptive statistics, Exploratory Factor Analysis and Structural Equation Modeling. The most important results are: in the sample, GSCM practices to the recovery of investment, as the resale of scrap and other waste materials, and the adequacy with legislation and auditing, obtained high scores; and research hypothesis (H1) was confirmed and considered statistically valid, indicating that, in fact, the evolution of environmental management influences the adoption of GSCM practices.

El objetivo en este estudio es comprobar si la evolución de la gestión ambiental se relaciona positivamente con la adopción de prácticas de gestión de la cadena de suministro verde o green supply chain management (GSCM) por parte de empresas del sector eléctrico electrónico en Brasil. Para ello, se realizó un estudio cuantitativo, por medio de una encuesta realizada en 100 empresas brasileñas del sector. Los datos obtenidos se procesaron mediante técnicas estadísticas descriptivas, análisis factorial exploratorio y modelos de ecuaciones estructurales. Los resultados más relevantes indican que, en la muestra, prácticas de GSCM orientadas hacia la recuperación de la inversión de las empresas, tales como la reventa de chatarra y otros desechos, además de cumplir con la legislación y auditoría ambiental, obtuvieron puntuación alta; asimismo, la hipótesis de investigación (H1) se confirmó y se consideró estadísticamente válida, lo que demuestra que, efectivamente, la evolución de la gestión ambiental influye en la adopción de prácticas de GSCM.

Na pesquisa apresentada, teve-se como objetivo verificar se a evolução da gestão ambiental se relaciona positivamente com a adoção de práticas de green supply chain management (GSCM) por empresas do setor eletroeletrônico do Brasil. Para fazer frente ao objetivo exposto, foi realizada uma pesquisa quantitativa, por meio de um levantamento survey, com cem empresas do setor eletroeletrônico brasileiro. Os dados coletados foram processados por meio de técnicas estatísticas descritivas, análise fatorial exploratória e modelagem de equações estruturais. Os resultados mais importantes da pesquisa foram: na amostra, práticas de GSCM orientadas para a recuperação dos investimentos das empresas, como a revenda de materiais inservíveis e outros resíduos, além da adequação à legislação e à auditoria ambiental, obtiveram médias elevadas; e a hipótese de pesquisa (H1) foi confirmada e considerada estatisticamente válida, indicando que a evolução da gestão ambiental influencia a adoção de práticas de GSCM.
Evidences of the relationship between the environmental management evolution and the adoption of green supply chain management practices in the Brazilian electronics sector
Evidencias de la relación entre la evolución de la gestión ambiental y la adopción de prácticas de green supply chain management en el sector eléctrico electrónico en Brasil
Keywords: Environmental management; Green supply chain management; Environmental management development; Electronic sector; Brazil; Gestión ambiental; Gestión de la cadena de suministro verde; Evolución de la gestión ambiental; Sector eléctrico electrónico; Brasil; Gestão ambiental; Green supply chain management; Evolução da gestão ambiental; Setor eletroeletrônico; Brasil